SISTEM TRANSMISI ULTRA-DENSE WAVE LENGTH DIVISION MULTIPLEXING - Harumi Yuniarti; Bambang Cholis Su’udi (Jetri : Jurnal Ilmiah Teknik Elektro, 2014)
Ultra long distance transmission systems - Dense Wave length Division Multiplexing (U-DWDM) is one of the fiber optic transmission systems are designed to provide large capacity and is able to transmit long distance range. Technology system design is made possible by simplifying the network architecture, as well as involving large-capacity network level, such as the use of a single network of 10 Gbps to 40 Gbps, increasing the number of wavelengths, as well as reducing the wavelength interval to extend the range of spectral systems (C-band L-band S -band). So the U-DWDM system design is a breakthrough fiber optic transmission system which is able to raise up to 160 wavelength. This technology utilizes a system SDH (Synchronous Digital Hierarchy) with Multiplexing existing signal sources. The design of this transmission devices used in telecommunications transmission services is a large-capacity transmission device and serves as a long-distance backbone designed in accordance with the conditions of the present and future as the development of optical networks, with flexible configuration. Keywords: Dense  Wavelength  Division Multiplexing (DWDM), Modulation, Return to Zero(RZ),  Forward  Error  Correction  (FEC),  Eribium  Dopped Fibre Amplification (EDFA), Distributed Raman Amplification (DRA). Sistem transmisi Ultra long distance-Dense Wave length Division Multiplexing (U-DWDM) merupakan salah satu sistem transmisi serat optik yang dirancang untuk menyediakan layanan berkapasitas besar dan mampu mentransmisi jangkauan jarak jauh. Teknologi rancangan sistem ini dimungkinkan dengan menyederhanakan arsitektur jaringan, sekaligus melibatkan tingkat jaringan berkapasitas besar, seperti pemanfaatan jaringan tunggal 10 Gbps ke 40 Gbps, meningkatkan jumlah panjang gelombang, serta mengurangi interval panjang gelombang dengan memperluas jangkauan sistem spektral (C-band L-band S-band). Sehingga rancangan sistem U-DWDM ini merupakan sebuah terobosan sistem transmisi serat optik  yang mampu meningkatkan  hingga 160-panjang gelombang. Kata Kunci: Dense Wavelength Division Multiplexing (DWDM), Modulation, Return to Zero (RZ),  Forward  Error  Correction (FEC), Eribium Dopped Fibre Amplification (EDFA), Distributed Raman Amplification (DRA)